EFEKTIVITAS SISTEM PENDIDIKAN DAN KURIKULUM BERBASIS PANCASILA DALAM MENYIAPKAN GENERASI EMAS BERDAYA SAING GLOBAL - Warlim, Warlim; Budhiati, Ida; Ramadhani Nalole, Suci (CV. Lafadz Jaya, 2025)
This study aims to analyse the effectiveness of the Pancasila-based education system and curriculum in preparing Indonesia's Golden Generation to be globally competitive. This study uses a literature review method to identify the factors that support and hinder the implementation of the Pancasila-based curriculum, as well as its impact on the character building and global competencies of students. The results of the analysis indicate that the Merdeka curriculum policy, tripartite collaboration, technology utilisation, teacher training, and resource availability are the main factors that strengthen the effectiveness of the Pancasila-based education system. However, disparities in implementation between regions, limited teacher competencies, low student participation, and the challenges of digitalisation and globalisation remain obstacles that need to be overcome. This study recommends the need for synergy among all stakeholders, enhanced teacher training, and strengthened school-family-community collaboration to optimise the effectiveness of the Pancasila-based education system in order to achieve the Golden Generation 2045 with global competitiveness and strong character.